Humoral Response Following Triple Dose of mRNA Vaccines Against SARS-CoV-2 in Hemodialysis Patients: Results After 1 Year of Follow-Up - Gallego-Valcarce, Eduardo; Shabaka, Amir; Leon-Poo, Mariana; Gruss, Enrique; Acedo-Sanz, Juan Manuel; Cordón, Alfredo; Cases-Corona, Clara; Fernandez-Juarez, Gema (Frontiers in Medicine, 2022)
Introduction COVID-19 is associated with an increased mortality in hemodialysis patients. Therefore, achieving a long-lasting effective immune response to SARS-CoV-2 vaccines is essential. This study describes the humoral immune response in hemodialysis patients following three doses of mRNA vaccines against SARS-CoV-2, and explores the factors associated with a sustained immune response. Materials and Methods We analyzed the monthly serological evolution of SARS-CoV-2 anti-S(RBD) antibodies for 1 year in 178 chronic hemodialysis patients who received three doses of SARS-CoV-2 mRNA vaccines. The primary outcome was sustained effective humoral response defined as anti-S(RBD) levels > 1,000 AU/ml after 4 months from the third dose. Multivariate logistic regression analyses were used to identify features associated with a sustained humoral immune response. Results After the initial two SARS-CoV-2 mRNA vaccine doses, 77.8% of patients showed an immediate effective humoral response, decreasing to 52.5% after 4 months. Antibody levels were significantly higher in COVID-exposed patients and HBV vaccine responders. After the third dose, 97% of patients showed an effective humoral response, and remained in 91.7% after 4 months. The mean monthly rate of antibody titer decline decreased from 33 ± 14.5 to 25 ± 16.7%. Multivariate regression analysis showed that previous exposure to COVID-19 and response to HBV vaccines were associated with an effective sustained humoral immune response. Conclusion Immunization with SARS-CoV-2 mRNA vaccines elicits an effective immediate humoral immune response in hemodialysis patients, with a progressive waning in antibody levels. A third booster dose enhances the immune response with significantly higher antibody levels and more sustained humoral immune response. COVID-naïve patients and patients without previous response to HBV vaccines are likely to benefit from receiving more booster doses to maintain an effective immune response.